Ancient zionism the biblical origins of the national idea - Erlich, Avi (New York, NY [u.a.] Free Press, 1995)
The ancient Hebrews, Erlich argues, invented a unique basis for social unity by forging an imaginative link between religion (or law), literary culture, and the specific land of Israel. In this conception, the land, the law, and the people of Israel are one, a living metaphor expressed in the idea of Zion. The unity of land, law, and literature created by the Hebrews has been one of the most potent historical metaphors ever devised, strong enough to maintain a sense of national identity among Jews for over two thousand years. Without this Jewish literary culture, Erlich argues, there could have been no state of Israel, no matter what efforts were made by modern Zionist ideologues
This book reads the ancient text with ancient eyes that make it startling and fresh for those conditioned to the "modern" view of national identity as based on either race or ideology. Modern Zionism, like modern nationalism generally, is a drastically impoverished descendant of this original Jewish nationalism, and Erlich concludes that many problems not only of Israel but of all modern nations struggling to define themselves in a changing world really stem from the loss of this vigorous ancient alternative
Introduction: The beginnings of intellectual nationalism -- Land and intellect -- Land and literacy -- Land and law -- Land and loot -- History and hell -- David in Zion -- Brickkiln and winepress -- Ritual in the land -- The wisdom of Solomon -- Prophecy in the land -- Jonah: landless and illiterate -- The ancient hatred of Zionism -- Esther: the Hebrew mind in Diaspora -- Zohar -- A bough over the wall -- Dry bones: Zion as tragicomedy -- Ancient Zionism and its moderns competitors.
Includes index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Palestine -- In the Bible